A typical phenomenon of cultivated land use in China's economically developed areas: Anti-intensification in Jiangsu Province. (March 2021) - Liang, Xinyuan; Jin, Xiaobin; Sun, Rui; Han, Bo; Liu, Jing; Zhou, Yinkang
Highlights: We propose a concept of the anti-intensification of cultivated land use (ACLU). ACLU is a typical phenomenon in China's economically developed areas. ACLU contains recessive and dominant connotations. ACLU has significant socioeconomic stages and regional differences. Abstract: Cultivated land utilization is related to national food security and sustainable development. The anti-intensification of cultivated land use (ACLU) is a typical phenomenon involving recessive function loss and the potential marginalization process in China's economically developed areas. This paper summarized ACLU using theoretical and empirical research paradigms and revealed the connotation and characteristics of ACLU from the three-dimensional perspective of input-utilization-output. The results confirm ACLU, which includes two connotations of recessive and dominant, is associated with the intensification process and mainly occurs in economically developed areas. As a result of the influence of labor and capital input weakening per unit area caused by the stakeholders' behaviors of cultivated land use, ACLU mainly presents extensive utilization such as agricultural land type conversion and planting system changes. Taking Jiangsu Province as a case, the ACLU trend shows a regular pattern of changing from a rapid rise in the early stage to a gradual decline in the later stage with socioeconomic development. Concurrently, ACLU has significant regional differences, and river network density is an essential factor affecting Jiangsu's provincial ACLU trend. Besides, the natural environment and socioeconomic factors have different performance characteristics in northern, central, and southern Jiangsu, and socioeconomic contributions have gradually increased from north to south. ACLU is mainly affected by human factors such as regional policy implementation and urban-rural dual structure system, leading to regional differences in ACLU's stage and performance characteristics. Overall, this study can offer ideas for exploring the sustainable intensification path of regional agricultural land utilization under the current rural revitalization background. Further, it can provide scientific reference for cultivated land use management, crop planting mode adjustment, and agricultural land consolidation direction in economic development pilot zone.